ANALISA CUSTOMER VALUE DAN CUSTOMER EXPERIENCE TERHADAP CUSTOMER LOYALTY DENGAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING (Studi Pada Waroeng Spesial Sambal Cabang Purwokerto) - Ariningsih, Kuswanti; Muji Rahayu, Tri Septin (Media Ekonomi, 2015)
This research was based on the comptitive business condition in restaurant business that wasgetting more competitive, therefore the corporates had to make a new marketing strategy to stay andachieve he higher market. This research aimed to test the effect of customer value and customerexperience toward customer loyalty with customer satisfaction as intervening variable.The data were gained by questionnaire method to the 110 respondent of waroeng spesialsambal cabang purwokerto with purposive sampling. The result of the research showed that not all ofthe hypotheses could not be accapted. Out of the 5 (five) hypotheses accepted hypotheses. The resultof H1, H2, H3 showed that customer value and customer experience partialy and simultane affectedsignificantly of the customer experience to customer loyalty. Sobel test showed that from both variablescustomer value and customer experience proved that customer vaue and customer experience hadmediated effect.Key words: customer value, customer experiece, customer satisfaction, customer loyalty